Ontology of social networking sites related to Ibn Khaldun’s thoughts: evaluation approaches - Mohamed Najid, Mohamad Hafizuddin; Zulkifli, Zahidah; Othman, Roslina; Rokis, Rohaiza; Salahuddin, Ashraf Ali (Penerbit UMK, 2022)
This paper aims to evaluate two essential aspects of ontologies: consistency and correctness. Thus, this research focuses on the evaluation activities performed during the ontology development of ethical issues in social networking sites based on Ibn Khaldun’s thoughts. The evaluation stage consists of four sub-stages: validation and verification following the guideline and criteria; SPARQL query testing, and user assessment. Three experts were interviewed to validate the ontology and verify the semantic relationship. The evaluation phase met the criteria referred to in this research and all the execution in the SPARQL query were successful. For users' assessment, 62% of the results were categorised as suitable. Ontology evaluation approaches signify the importance to ensure the accurate sources and trustworthiness of Ibn Khaldun’s thoughts suggested to users to assist them to deal with the challenge and issues in accessing the social media platform using the ontology concepts.